2018
DOI: 10.1016/j.jbiomech.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Ascending thoracic aorta aneurysm repair induces positive hemodynamic outcomes in a patient with unchanged bicuspid aortic valve

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Ten studies provided 4D flow data on ARR for patients with BAV aortopathy (47,(51)(52)(53)(54)(55)(56)(57)(58)(59). The majority (nine) of these studies used a valve-sparing technique (47,(52)(53)(54)(55)(56)(57)(58)(59), with two using a mechanical prosthesis (47,51) and two comparing valve-sparing and valved ARR (47,52). All ARR studies reported data on the flow pattern or helicity in the aortic arch, with four also reporting WSS, and four reporting PV values.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies provided 4D flow data on ARR for patients with BAV aortopathy (47,(51)(52)(53)(54)(55)(56)(57)(58)(59). The majority (nine) of these studies used a valve-sparing technique (47,(52)(53)(54)(55)(56)(57)(58)(59), with two using a mechanical prosthesis (47,51) and two comparing valve-sparing and valved ARR (47,52). All ARR studies reported data on the flow pattern or helicity in the aortic arch, with four also reporting WSS, and four reporting PV values.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using a rigid wall often focus on geometric effects using patient-specific parameters without the additional computational expense and required material properties needed for FSI. For example, studies using rigid walls revealed that patients with bicuspid aortic valve (BAV) have complex blood flow patterns that cause higher and uneven wall shear stresses, increasing the potential for TAA formation (Youssefi et al, 2017;Condemi et al, 2018;Edlin et al, 2019). Mendez et al (2018) simulated blood flow in BAV TAAs using both rigid walls and FSI, finding non-significant differences in helical flow, but significantly lower estimated pressure in CFD simulations.…”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…Youssefi et al used computational fluid-only biomechanical models to investigate the impact of inflow velocity profiles on hemodynamics of the thoracic aorta [ 29 ]. Condemi et al performed patient-specific computational fluid dynamics analysis to obtain the effect of hemodynamics on the ascending thoracic aortic aneurysm risk of rupture [ 30 ] and also investigated the hemodynamic alterations for a patient who was treated by only ascending aorta replacement preserving the BAV [ 31 ]. Underhill et al constructed image-based computational models by integrating plaque morphology, components, and mechanical stress/strain conditions to assess the vulnerability of human atherosclerotic carotid plaques [ 32 ].…”
Section: Introductionmentioning
confidence: 99%